AN ASSESSMENT OF PUBLIC AND PRIVATE BENEFITS OF ORGANIC FARMING IN PAKISTAN - 1 M. I. U. Husnain; 2M. Khan; 3H. Z. Mahmood (Journal of Animal and Plant Sciences, 2017)
Despite the acknowledged advantages of organic farming, questions remain about its productivity differential and financial viability to its counterpart conventional farming. We test this claim in Pakistan, by comparing the productivity and profitability of organic and conventional farms that grow two major crops, wheat and rice, based on primary data collected from 444 (220 organic & 224 conventional) farms located in three districts of Punjab province. We find that growing organic crops is at least as profitable as conventional crops despite their low yields due to lower input costs and higher commodity prices. The Benefit Cost Ratio is also higher for organic crops which suggest that farmers can get higher profits by moving from conventional to organic crops. Overall, input costs are 20% and 10% lower in organic wheat and rice farms relative to their conventional counterparts. Soil nutrient tests show that organic farms tend to better conserve soil fertility and system stability than conventional farms. Based on these private and public benefits, we argue that organic agriculture should be encouraged to ensure sustainable agricultural practices in Pakistan. Farmers’ tentative adoption of commercial organic farming will largely depend on how demand for organically farmed food continues to grow.
Keywords: Organic Farming; Conventional Farming; Wheat; Rice; Fertilizers; Pesticides